Estimating cost of rearing dairy young stock in selected farms in Malaysia - Ang, Xin Tong (2022)
Dairy young stock must be readily available in dairy farms to replace culled dairy cows. Proper management practices are crucial to ensure the successful growth of the young stock. However, the dairy young stock does not get optimal attention from dairy farmers because rearing usually takes at least 24 months to generate an income for the farmer. Thus, this study aims to estimate the costs of rearing dairy young stock from birth to the first calving age. First, a questionnaire-based survey was conducted in Keningau, Sabah from July to August 2019 at 13 noncommercials and 1 commercial dairy farm. Secondly, the bodyweight data of individual dairy young stock from the non-commercial farms (n=76) and two commercial dairy farms, each at Sabah (n=150) and Johor (n=73) were collected and analysed. The Gompertz function, W (t) = A * Exp (-B * Exp (-K * t)), was used to predict the bodyweight of the dairy young stock. The survey results and the bodyweight data were summarized in Microsoft Excel and were analysed using Statistical Package for Social Science (SPSS) version 25.0 (IBM). Finally, a stochastic bio-economic model at animal level was developed in Microsoft Excel (Microsoft Corp. Redmond, WA, USA) using @Risk add-in software (Palisade Corporation, Ithaca, NY, USA). Inputs for the model were based on chapter 3 and 4, literature and expert opinion. The survey results showed the average first calving age were 35 ± 1.48 months and 24 months in non-commercial and commercial dairy farms, respectively with an average cost of rearing of RM4,320 per heifer which only include cost of milk and concentrate. The average first calving weight of dairy young stock predicted using the Gompertz model was 430kg across different farm management system. The stochastic bio-economic model estimated the average total cost to rear a dairy young stock from birth until first calving age across different farm management systems is RM7,681.15 per heifer including the average mortality cost of RM2.65 per survived heifer. In conclusion, the results of this this study have revealed differences in the first calving age and costs of rearing dairy young stock amongst non-commercial and commercial dairy farms in Malaysia.